2014 Tenth International Conference on Intelligent Information Hiding and Multimedia Signal Processing 2014
DOI: 10.1109/iih-msp.2014.29
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Turtle Shell Based Scheme for Data Hiding

Abstract: Data hiding is a well-known technique which embeds the secret data into a digital media. Most of the existing schemes either have the low image quality, or provide the restricted embedding capacity. In this paper, a new data hiding scheme based on turtle shell is proposed to obtain better image quality and higher embedding capacity. In the proposed scheme, a secret digit is embedded into each cover pixel pair with the guidance of the turtle shell. Experimental results reveal that the proposed scheme ensures no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
105
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(106 citation statements)
references
References 16 publications
(37 reference statements)
1
105
0
Order By: Relevance
“…It can be observed that the proposed scheme obviously outperforms the other four in terms of the embedding capacity and image quality. To be more detailed, the embedding capacity of the proposed scheme (i.e., 2.5 bpp) is much higher than that of [23] (i.e., 1.5 bpp), just with a slight decrease of PSNR. The image quality of the proposed scheme is better than that of [24,25], even with a higher embedding capacity.…”
Section: Resultsmentioning
confidence: 99%
“…It can be observed that the proposed scheme obviously outperforms the other four in terms of the embedding capacity and image quality. To be more detailed, the embedding capacity of the proposed scheme (i.e., 2.5 bpp) is much higher than that of [23] (i.e., 1.5 bpp), just with a slight decrease of PSNR. The image quality of the proposed scheme is better than that of [24,25], even with a higher embedding capacity.…”
Section: Resultsmentioning
confidence: 99%
“…Shell based scheme used in [7] for data hiding that increase embedding capacity and with good visual quality of stegoimage. This scheme called turtle, which uses hexagon shaped shell to update pixel pairs in the cover image.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, it outperforms EMD, Chang et al's scheme [8] and Hong et al's scheme [9] in better image quality under the same embedding capacity. Later, Liu et al [12] improved Chang et al's scheme [11] by constructing a location table from the turtle shell-based reference matrix to guide the modification of cover pixel pairs. This scheme achieves very good image quality above 45 dB and is better than Chang et al's scheme [11] with higher embedding capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results showed that EMD-2 is superior to EMD in larger payloads with similar image distortions. In 2014, Chang et al [11] proposed a novel data hiding scheme originating from EMD and turtle shell structure. The binary secret stream can be embedded directly in such a way that three secret bits are embedded in a pair of consecutive cover pixels with the guidance of a reference matrix based on turtle shells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation